2016
DOI: 10.5152/balkanmedj.2015.15084
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effect of Leptin on Spatial Learning and Memory in Streptozotocin-Induced Diabetic Rats

Abstract: Background: Diabetes mellitus is a chronic disease which may be accompanied by cognitive impairments. The expression of the obesity gene (ob) is decreased in insulin-deficient diabetic animals and increased after the administration of insulin or leptin. Plasma leptin levels are reduced in the streptozotocin (STZ)-induced diabetic rats. Therefore, the deleterious effects of diabetes on memory may be due to the reduction of leptin. Aims: Investigate the effect of subcutaneous injection of leptin on spatial learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 30 publications
2
8
0
Order By: Relevance
“…These results are in line with the findings of the study conducted by Ghasemi et al 12 Ghasemi and his colleagues in their study showed that leptin administration in the same dose as the one used in our study brought about a decrease in the levels of blood glucose in the rats. This decline in the blood glucose paralleled the improvement in cognition seen in their study.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…These results are in line with the findings of the study conducted by Ghasemi et al 12 Ghasemi and his colleagues in their study showed that leptin administration in the same dose as the one used in our study brought about a decrease in the levels of blood glucose in the rats. This decline in the blood glucose paralleled the improvement in cognition seen in their study.…”
Section: Discussionsupporting
confidence: 94%
“…Rats after the successful induction of diabetes were subjected to behavioural assessment in the T maze test after completing the required treatment lengths. 12…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the past decade, researchers showed a role for leptin in neuroprotection and hippocampal neurogenesis. In animal models, leptin administration facilitates learning and alter synaptic plasticity (Moult et al, 2010;Luo et al, 2015;Ghasemi et al, 2016). Additionally, this adipokine attenuates Tau hyperphosphorylation in neuronal cells and protects against Aβ-induced neurotoxicity in cellular models (Garza et al 2008, Doherty et al, 2013Liu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, the brain (mostly hypothalamus) is not the only target for leptin and other adipokines, as well as the food intake is not the only biological e ect of these adipokines. Rather, some adipokines support various metabolic and cognitive functions and exert both metabo-and neurotrophic actions (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Current data of adipose-derived neuroendocrine and neurotrophic factors are summarized in Tables 1, 2.…”
Section: Adipobiology 7 2015mentioning
confidence: 99%